Analysis total plate count (tpc) and organoleptic test on seaweed chips. (April 2020) - Zainuri, M; Endrawati, H; Winarni, S; Arifan, F; Setyawan, A; Hapsari, H P
Abstract: Some seaweed in Indonesia has economic value, such as jelly-producing seaweed, namely Gracilaria, Gelidium, Gelidiopsis, and Hypnea, carrageenan-producing seaweed, namely Euchema spinosium, Euchema cottonii, Euchema striatum, algin-producing seaweed, that Sargassum, Macrocystis and Lessonia. This study aims to determine the microbial contamination on seaweed chips with total plate count (TPC) method and organoleptic test. The samples used were Sargassum chips and Eucheuma cottonii chips with variations in drying of seaweed raw materials. Seaweed chips samples were tested for microbial contamination. The number of microbial contamination on Sargassum chips was 2.6 × 102 CFU/ml and E. cottonii chips was 2.8 × 102 CFU/ml. Based on TPC analysis concluded that Sargassum chips and E. cottonii chips were both safe for consumption because the amount of microbial contamination does not exceed the maximum limit of the Indonesian National Standard, which is 105 CFU/ml. Based on organoleptic tests, Sargassum chips were preferable than E. cottonii chips.